Baguio berde plant conservatory and plant nursery - Concepcion, Christelle May Y. (College of Architecture, University of the Philippines Diliman, 2018)
This Comprehensive Design Project focuses on the sustainability of the botanical life in Baguio City, which is a major tourist destination in the Philippines that has numerous parks and forests for people's recreation and livelihood. The challenge was to observe the city and determine an apparent problem and solve it through architecture. With the apparent declining conditions of the environment, and the lack of proper facility that can sustain the seedlings needed for the parks and forests, the proposal of the Baguio Berde: Plant Conservatory and Plant Nursery aims to solve these problems. This facility was designed as an urban intervention with a threefold agenda, environmental preservation, tourism, and education. The design process by which the architectural forms and concepts were derived were rooted from context-based explorations of the site's geologic form and structure, thus resulting to curves that mimic the site. With the final form created, explorations of new structural methods were created in order to meet design goals of the project. The project looks into the future, and as such, it's unconventional aesthetics, is a hopeful symbol of what the city can become: a clean and green place activated by nature and the people.